2012
DOI: 10.1051/0004-6361/201219475
|View full text |Cite
|
Sign up to set email alerts
|

Herschel/PACS observations of young sources in Taurus: the far-infrared counterpart of optical jets

Abstract: Context. Observations of the atomic and molecular line emission associated with jets and outflows emitted by young stellar objects provide sensitive diagnostics of the excitation conditions, and can be used to trace the various evolutionary stages they pass through as they evolve to become main sequence stars. Aims. To understand the relevance of atomic and molecular cooling in shocks, and how accretion and ejection efficiency evolves with the evolutionary state of the sources, we will study the far-infrared c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
108
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(123 citation statements)
references
References 76 publications
(132 reference statements)
15
108
0
Order By: Relevance
“…Podio et al (2012) showed that for four of these sources (T Tau, DG Tau A, FS Tau and RW Aur) the oxygen emission at 63 µm is spatially extended. They compared shock and disk model predictions for the fluxes of the [O ] 63 µm line, and found that these are likely dominated by jet/outflow emission.…”
Section: Oxygen Line Fluxesmentioning
confidence: 99%
“…Podio et al (2012) showed that for four of these sources (T Tau, DG Tau A, FS Tau and RW Aur) the oxygen emission at 63 µm is spatially extended. They compared shock and disk model predictions for the fluxes of the [O ] 63 µm line, and found that these are likely dominated by jet/outflow emission.…”
Section: Oxygen Line Fluxesmentioning
confidence: 99%
“…15. Our calculations for Class 0 and I sources are supplemented by results from Podio et al (2012) for the Class II sources (average cooling of DG Tau A and RW Aur) that drive prominent jets. Similar to the selected line flux trends, a factor of 10 decrease in the CO and H 2 O cooling is detected for the Class I sources as compared to the Class 0 objects.…”
Section: Evolution From Class 0 To Class Imentioning
confidence: 99%
“…An overview of the detected atomic and molecular species is shown in The HD J = 1−0 line at 112 μm has been detected toward TW Hya with a flux of 6.3 (±0.7) × 10 −18 W m −2 after deep integration (Bergin et al 2013 Podio et al (2012). Table 3 refers to the on-source position only (spectrum extracted from the central spaxel and corrected for PSF-loss, see Appendix D).…”
Section: Overviewmentioning
confidence: 99%
“…In this case, a further contribution to the OH lines may come from a shock associated with the molecular outflow/jet associated with the system. Indeed, compact warm OH emission has been observed to be associated with outflows in embedded young stellar objects (van Kempen et al 2010;Wampfler et al 2010Wampfler et al , 2013Podio et al 2012;Karska et al 2013). Further analysis including the mid-infrared lines (from Spitzer) is needed to disentangle the disk/outflow origin of OH for these systems.…”
Section: Origin Of Far-ir Emission Linesmentioning
confidence: 99%